2021
DOI: 10.1155/2021/1642852
|View full text |Cite
|
Sign up to set email alerts
|

SPP1 Regulates Radiotherapy Sensitivity of Gastric Adenocarcinoma via the Wnt/Beta-Catenin Pathway

Abstract: Purpose. Radiotherapy has been widely applied for the treatment of locally advanced and metastatic gastric adenocarcinoma (GAC). The aberrant expression of secreted phosphoprotein 1 (SPP1) is involved in radiosensitivity in a variety of cancers. The present study aims to characterize the clinical significance of SPP1 expression in GAC and its role and underlying mechanism of radiosensitivity. Methods. The SPP1 expression in GAC tissues and pericarcinomatous tissues was determined by QRT-PCR and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…It is known to regulate radiotherapy sensitivity in gastric adenocarcinoma through the Wnt/β-catenin pathway. 28 Similarly, our results revealed that a high expression of SPP1 occurs in fibrotic liver tissue of BDL rats and activated LX-2 cells, and it is related to the TGF-β1/Smads signaling pathway, as indicated by KEGG and GO analysis.…”
Section: Discussionsupporting
confidence: 69%
“…It is known to regulate radiotherapy sensitivity in gastric adenocarcinoma through the Wnt/β-catenin pathway. 28 Similarly, our results revealed that a high expression of SPP1 occurs in fibrotic liver tissue of BDL rats and activated LX-2 cells, and it is related to the TGF-β1/Smads signaling pathway, as indicated by KEGG and GO analysis.…”
Section: Discussionsupporting
confidence: 69%
“…In GBM, ID1 overexpression increased radioresistance [ 17 ] , and ID1 expression levels predicted poor overall survival and knockdown of ID1 increased radiosensitivity in vitro [ 18 ] . One of the other genes from our RNA-seq data shown to regulate radiation sensitivity was SPP1 in gastric adenocarcinoma [ 21 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Any abnormalities in the key components of this pathway may cause Wnt/β-Catenin activation, leading to increased cell proliferation and in turn to tumorigenesis [ 47 ]. Wnt signaling has also been associated with the effects of radiotherapy on tumors [ 48 , 49 ]. Given the tight association among Wnt signaling, radiotherapy, and CRC, we speculated that the Wnt pathway was likely to be involved in the response to radiotherapy in cetuximab-resistant CRC.…”
Section: Discussionmentioning
confidence: 99%